Promising Remission with Reduced Bevacizumab and Pembrolizumab Dosage in a Patient with AT-rich Interaction Domain 1A Mutated Ovarian Clear-cell Carcinoma Refractory to Chemotherapy - Cheng-Wei Huang; Ruo-Han Tseng (Journal of Cancer Research and Practice)
Patients with ovarian clear-cell carcinoma have limited treatment choices, because they are resistant to the standard chemotherapeutic agents used in ovarian cancer. The phase II KEYNOTE-100 trial revealed that pembrolizumab monotherapy demonstrated a 15.8% objective response in patients with ovarian clear-cell carcinoma in the subgroup analysis, which is much higher than that of other histology subtypes of ovarian cancer. Immune checkpoint inhibitors may play a new role in the treatment of these malignancies. Genetic analyses revealed a significant proportion of ovarian clear-cell carcinoma carrying the AT-rich interaction domain 1A protein (ARID1A) mutation. The association between a higher frequency of ARID1A mutation and a higher response to immune checkpoint inhibitors in ovarian clear-cell carcinoma opens a new research topic. Herein, we report a patient with ovarian clear-cell carcinoma refractory to platinum-based chemotherapy, who was treated with a reduced dose of bevacizumab and pembrolizumab combination therapy and achieved a complete treatment response.